Molecular phylogeny and systematics of Blue and Grey Noddies (Procelsterna). (6th March 2016) - Cibois, Alice; Thibault, Jean‐Claude; Rocamora, Gérard; Pasquet, Eric
Abstract : We used a mitochondrial and nuclear DNA phylogeny to evaluate the relationships among all noddies ( Anous and Procelsterna, Laridae) and to clarify their classification. The Lesser Noddy Anous tenuirostris and Black Noddy Anous minutus form a pair of closely related sister‐species, as do the Blue Noddy Procelsterna albivitta and Grey Noddy Procelsterna cerulea . Blue and Grey Noddies are embedded within the dark noddies and are the sister‐clade to the Lesser and Black Noddies, indicating that the genus Anous in its current definition is not monophyletic. Thus, we propose to merge all noddies into the genus Anous Stephens1826, and to consider Procelsterna Lafresnaye1842 as a junior synonym.